2013
DOI: 10.1177/002795011322500104
|View full text |Cite
|
Sign up to set email alerts
|

Credit Dynamics and Financial Globalisation

Abstract: This paper reviews the impact of financial globalisation on credit dynamics. In particular, it argues that financial globalisation fundamentally alters credit demand and credit supply, since borrowers and lenders have foreign options as well as domestic options in terms of the selection of projects and funding sources. The rapid accumulation of large cross-border debt positions was a central feature in the boom phase of the European credit cycle during 2003–8 and has influenced the nature of the post-2008 fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Besides amplitude, the composition of capital inflows also matters for fragility. Research has shown a strong link from net debt flows to domestic credit expansion in a range of countries and periods (Allen, 2005, and Lane, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Besides amplitude, the composition of capital inflows also matters for fragility. Research has shown a strong link from net debt flows to domestic credit expansion in a range of countries and periods (Allen, 2005, and Lane, 2013).…”
Section: Introductionmentioning
confidence: 99%